Pelatihan Pembuatan Buku Cerita Bergambar bagi Guru PAUD di Kelurahan Braja Asri Kabupaten Lampung Timur - Khomsiyati, Siti; Susanti, Septiani Selly; Fatimah, Siti (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
The community service mentoring program aims to improve the skills of educators who teach early childhood. Their focus is on producing picture storybooks that serve as innovative and instructive learning tools, while still considering the unique characteristics of young children. These picture storybooks play a crucial role in fostering growth in areas such as language, thinking, social skills, emotional intelligence, and fostering an interest in reading in children from an early age. This community service program is implemented using a training approach. This includes delivering information, conducting discussions, providing guidance, and offering opportunities for practical application. The training covers various elements of storytelling, including the goals and methods for developing and sharing stories in educational settings. The teachers participating in the mentoring program are mentors from three early childhood education schools. These teachers faced challenges in creating learning resources that incorporate storytelling techniques. The results of the activity showed that the teachers improved their understanding and skills in creating picture storybooks that are relevant and tailored to children's needs. Furthermore, the training also motivated educators to adopt a more creative mindset in producing their own learning materials. With this mentoring, it is hoped that this community service project will have a positive impact on improving the standards of early childhood education and fostering a strong dedication to literacy from an early age.